2012
DOI: 10.4162/nrp.2012.6.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retrograded rice on weight control, gut function, and lipid concentrations in rats

Abstract: The effects of retrograded rice on body weight gain, gut functions, and hypolipidemic actions in rats were examined. When the retrograded rice was produced by repetitive heating and cooling cycles, it contained significantly higher amounts of resistant starch (13.9 ± 0.98%) than is found in common rice (9.1 ± 1.02%) (P < 0.05). Sprague-Dawley rats were fed either common rice powder or retrograded rice powder, and mean body weight gain was significantly lower in the retrograded rice group (P < 0.05). The liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
7
0
4
Order By: Relevance
“…Jayawardena, Herath, Watawana, and Waisundara () also reported that TS content of cooked rice grain did not change during storage at room temperature (25–28 °C). The RS content of starchy foods has been reported to increase during storage at low temperatures (Ha et al, ; Jayawardena et al, ; Leeman et al, ). In contrary, Eerlingen, Crombez, and Delcour () showed that RS content of wheat starch formed initially increased quickly at 0 °C, however, maximum yield of RS content formed at 0 °C was lower than the RS obtained at storage temperatures of 68 and 100 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jayawardena, Herath, Watawana, and Waisundara () also reported that TS content of cooked rice grain did not change during storage at room temperature (25–28 °C). The RS content of starchy foods has been reported to increase during storage at low temperatures (Ha et al, ; Jayawardena et al, ; Leeman et al, ). In contrary, Eerlingen, Crombez, and Delcour () showed that RS content of wheat starch formed initially increased quickly at 0 °C, however, maximum yield of RS content formed at 0 °C was lower than the RS obtained at storage temperatures of 68 and 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Some retrograded starch can be regarded as an effective ingredient for the prevention of obesity, and type II diabetes, and so forth (Birt et al, ; Homayouni et al, ). Ingestion of retrograded cooked rice has been linked to lowering body weight gain; and improving lipid profiles and gut function in rats (Ha, Han, & Kim, ). The cold storage of other starchy foods such as potato has also been observed to significantly increase their RS content (Leeman, Östman, & Björck, ).…”
Section: Introductionmentioning
confidence: 99%
“…3 are 8.0-8.5 and 10-13%, respectively (Zeng et al, 2013). When retrograded rice was produced by repeated heating and cooling cycles, it contained significantly higher amounts of resistant starch (13.9 ± 0.98%) than is found in common rice (9.1 ± 1.02%) (Ha et al, 2012). In some products, retrogradation can provide a desirable quality such as in the manufacture of rice stick noodles, resistant starch type 3 croutons, and breadcrumbs (Charoenrein and Udomrati, 2013).…”
Section: Resistant Starch and Total Alkaloids In Ricementioning
confidence: 97%
“…Secara ilmiah hal tersebut dapat dijelaskan sebagai akibat perubahan suhu yang kemudian mempengaruhi stuktur pati pada nasi sehingga pati resisten yang terkandung nasi menjadi meningkat kadarnya. 8 Pati resisten (starch resisten) adalah pati yang tidak tercerna dengan baik dalam usus halus tapi terfermentasi pada usus besar oleh mikroflora. Pati resisten terdapat dalam berbagai bentuk dan tingkatan stabilitas.…”
Section: Journal Of Nutrition Collegeunclassified
“…Kadar pati resisten pada nasi putih kemarin (teretrogradasi) yaitu 13,9±0,98, sedangkan kadar pati resisten pada nasi yang baru matang yaitu 9,1±1,02. 8 Penelitian tahun 2003 (in vitro) menunjukkan nasi yang disimpan pada suhu 4 o C selama 24 jam memiliki Glycemic Index (GI) dan tingkat kecernaan pati yang lebih rendah dibandingkan nasi yang baru matang (tidak mengalami retrogradasi). 19 Berdasarkan informasi tersebut, peneliti mencoba untuk meneliti efek dari nasi putih baru matang dengan nasi putih kemarin terhadap kadar glukosa darah ½, 1, dan 2 jam postprandial.…”
Section: Journal Of Nutrition Collegeunclassified